2022
DOI: 10.1039/d2ee01844f
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-assisted ultrafast flash sintering of high-performance and flexible silver–selenide thermoelectric devices

Abstract: The first machine learning-assisted ultrafast flash sintering of flexible silver–selenide TE devices. Bayesian optimization of flash sintering variables led to a PF of 2205 μW m−1 K−2 and a zT of 1.1 at room temperature realized with a sintering time less than 1.0 second.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 61 publications
(96 reference statements)
1
40
0
Order By: Relevance
“…Furthermore, the sintering treatment can effectively reduce the n of 1.14 × 10 19 cm −3 of the unsintered film to 7.3 × 10 18 cm −3 of the film sintered under optimum variables. 160 The reduced n leads to a high S of −161.7 μV K −1 and a moderate σ of 840 S cm −1 at room temperature. Moreover, the bending test result suggested that the decrement after 1000 bending cycles with a bending radius of 5 mm was less than 9%, indicating the excellent robustness of the sintered film.…”
Section: Device Designsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, the sintering treatment can effectively reduce the n of 1.14 × 10 19 cm −3 of the unsintered film to 7.3 × 10 18 cm −3 of the film sintered under optimum variables. 160 The reduced n leads to a high S of −161.7 μV K −1 and a moderate σ of 840 S cm −1 at room temperature. Moreover, the bending test result suggested that the decrement after 1000 bending cycles with a bending radius of 5 mm was less than 9%, indicating the excellent robustness of the sintered film.…”
Section: Device Designsmentioning
confidence: 97%
“…258,259 A data-driven algorithm such as Bayesian optimization (BO) was utilized in a high-throughput experiment to accelerate the discovery of the optimum variables of the fabrication process of Ag 2 Se films. 160…”
Section: Device Designsmentioning
confidence: 99%
See 3 more Smart Citations